Pengembangan Media Pembelajaran Interactive Pada Mata Kuliah Pendidikan Kewarganegaraan - Harry Surahman (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
This study aims to develop interactive learning media based on edutainment in the civic education course for Indonesian Language Study Program students at IKIP Budi Utomo Malang. Whereas the research target can be used as a role model for citizenship education teachers in Malang in developing edutainment-based interactive learning media in schools. The research development model uses ADDIE which consists of five main phases, namely (A) analysis, (D) essay, (D) development, (I) implementation, and (E) valuation. Analysis (analysis) analyzes the need for the development of new learning media and analyzes the feasibility and requirements for developing new learning media, Design (design) is a systematic process that starts from determining learning themes, learning objectives, selecting media elements such as text, audio, visual and videos, designing learning materials and learning outcome evaluation tools, Development (development) In the development stage, the conceptual framework is realized into a product that is ready to be implemented. Implementation At this stage a learning media design that has been developed in real situations is implemented. namely in class, Evaluation (assessment) Evaluation is used to measure how far students master the learning material. The results of this study indicate that the Edutainment-Based Interactive Learning Media developed in the civic education course using the Android program has valid and feasible criteria for use. Learning carried out by implementing Edutainment-Based Interactive Learning Media can improve student learning outcomes.